Associations between local land use/land cover and place-based landscape service patterns in rural Tanzania - Vesa Arki; Joni Koskikala; Nora Fagerholm; Danielson Kisanga; Niina Käyhkö (Elsevier Ltd, 2022)
Securing reliable flows of landscape services is a vital prerequisite for sustaining well-being, especially in the rural Global South, where livelihoods of local communities are dependent on the surrounding village landscapes. To support sustainable landscape development strategies, increased understanding is needed on how landscape services are associated with physical landscapes. In this paper, we studied how place-based landscape services are spatially associated with local land use/land cover (LULC) patterns in three rural villages in the Southern Highlands of Tanzania. We mapped the spatial distribution of eight provisioning and one cultural landscape service indicators through participatory mapping and identified their associations with the local LULC patterns using chi-square residual and correlation analysis. Based on our results, LULC patterns are significantly associated with landscape service patterns. Although local realities and interactions have created unique association patterns, some commonalities were found in all villages. This suggests that spatial information on LULC patterns could be used as a proxy for landscape service patterns at broader scales.